The Effect of Financial Policy, Managerial Ownership, Profitability, and Company Size on Company Value in Automotive and Component Sub-Sector Companies Registered in Indonesia Stock Exchange Period 2014-2018 - Tieka Trikartika Gustyana; Ramadhan Alfian Candra; Dewi Andrieta Shintia; Nugraha Nugraha (Jurnal Manajemen Indonesia, 2021)
The aim of each company is to increase company value which can maximize shareholders’ wealth. The factors that can affect the company value are financial policies consisting of investment decisions, financial leverage and dividend policies. In addition to financial policy, there are other factors that can affect a company's value, namely managerial ownership, profitability, and company size. Therefore, this study aimed to examine the effect of financial policy, managerial ownership, profitability, and company size on company value in the automotive and component sub-sector companies registered in Indonesia Stock Exchange in 2014-2018. The data analysis techniques used in this study were multiple linear regression analysis and hypothesis testing using t test, F test, and coefficient of determination. The result shows that partially investment decisions, dividend policy, managerial ownership, and company size had no effect on company value, while financial leverage and profitability had effect on company value. Simultaneously investment decisions, financial leverage, dividend policy, managerial ownership, profitability, and company size had effect on company value. Keywords— Financial Policy; Managerial Ownership; Profitability; Company Size; Company Value.